2008
DOI: 10.3324/haematol.12297
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes and the risk of non-Hodgkin's lymphoma and multiple myeloma in the European Prospective Investigation into Cancer and Nutrition

Abstract: BackgroundNon-Hodgkin's lymphomas are a heterogeneous group of neoplasms arising from the lymphopoietic system including a wide range of subtypes of either B-cell or T-cell lymphomas. The few established risk factors for the development of these neoplasms include viral infections and immunological abnormalities, but their etiology remains largely unknown. Evidence suggests that certain medical conditions may be linked, through immunosuppression, to the risk of nonHodgkin's lymphoma. Multiple myeloma is a neopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 46 publications
0
36
1
Order By: Relevance
“…Although results in the literature are contradictory, in a recent study conducted by Khan et al (2008) there was no association between self reported diabetes and multiple myeloma whereas the highest level of postload glucose was associated with risk of mortality from multiple myeloma (HR, 3.06; 95% CI, 1.05-8.93) in another study by Chiu et al (2006). This is in contrast with observations of other studies based in Asia (Vineis et al 2000).…”
Section: Resultscontrasting
confidence: 56%
“…Although results in the literature are contradictory, in a recent study conducted by Khan et al (2008) there was no association between self reported diabetes and multiple myeloma whereas the highest level of postload glucose was associated with risk of mortality from multiple myeloma (HR, 3.06; 95% CI, 1.05-8.93) in another study by Chiu et al (2006). This is in contrast with observations of other studies based in Asia (Vineis et al 2000).…”
Section: Resultscontrasting
confidence: 56%
“…Three studies provided data on PTCL. 16,27,30 The OR for PTCL was 2.42 (95% CI, 1.24-4.72; P ϭ .009; I 2 ϭ 0%; supplemental Figure). There was an association seen in Asian (OR ϭ 3.21, 95% CI, 1.14-8.44; P ϭ .03) but not in European studies.…”
Section: Outcome Resultsmentioning
confidence: 99%
“…Four studies provided data on DLBCL and FL. 12,16,26,28 The OR for DLCBL was 1.16 (95% CI, 0.92-1.48; P ϭ .22; I 2 ϭ 28%). There was an association in European studies (OR ϭ 1.48, 95% CI, 1.10-2.01; P ϭ .01; I 2 ϭ 0%), but not in American studies.…”
Section: Outcome Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, exposure to a wide range of toxins as well as type 2 diabetes (T2D) and obesity have been suggested as important mediators of the complex process of myelomagenesis (Alexander et al 2007, Lope et al 2008, Wallin & Larsson 2011. Among these latter preventable factors, T2D has attracted significant attention since it has been consistently identified as a medical condition frequently found in MM patients (Khan et al 2008, Richardson et al 2009, Castillo et al 2012 and it is thought to influence the myelomagenesis through hyperglycaemia and insulin-dependent and -independent mechanisms (Xu et al 2014). In a recent well-powered meta-analysis, Castillo et al (2012) observed that T2D was significantly associated with an increased risk of developing the disease (Castillo et al 2012).…”
Section: Introductionmentioning
confidence: 99%